Using Workforce Information for Degree Program Planning in Texas - Goldman, Charles A.; Butterfield, Lindsay; Lavery, Diana Catherine; Miller, Trey; Daugherty, Lindsay (RAND Corporation, 2023)
This report for the Texas Higher Education Coordinating Board describes current practices in using workforce information for degree program planning in Texas and elsewhere, analyzes options for using workforce information, recommends promising practices, describes new data tools, applies these tools, and describes findings.